Coaching biomechanics interface: competition and training - Irwin, G.; Kerwin, D. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
Bridging the gap between the underlying biomechanical parameters that determine successful gymnastics performance, and the provision of meaningful information for coaches has been the challenge for sports biomechanists for decades. Conceptualising this fundamental relationship through the coaching-biomechanics interface draws on the cognitive processes of learning and understanding, combined with grounded scientific concepts, which help explain and increase understanding of gymnastic performance. As such the coaching-biomechanics interface begins with an examination of coaches' implicit knowledge highlighted through the conceptual models of skill learning and development (Irwin et al., 2005). Central to this model is the development of a mind set, a conceptual understanding of how a skill works. Coaches develop an understanding of how the skill works then aim to replicate the spatial and temporal characteristics of the final skill in the physical preparations, progressions and preparatory skills used in training.